Primitive revolution : restorationist religion and the idea of the Mexican Revolution, 1940-1968 - Dormady, Jason, 1975- (University of New Mexico Press, 2011)
In this intriguing study, Jason Dormady examines the ways members of Mexico's urban and rural poor used religious community to mediate between themselves and the state through the practice of religious primitivism, the belief that they were restoring.